2020
DOI: 10.1002/hrdq.21412
|View full text |Cite
|
Sign up to set email alerts
|

Resisting ableism in deliberately developmental organizations: A discursive analysis of the identity work of employees with disabilities

Abstract: People with disabilities, an understudied population in human resource development, are often constructed as deficient and unproductive in the workplace. Such a phenomenon can largely be attributed to ableism, which is intensified by the widespread organizational emphasis on productivity. With the recognition of people with disabilities as political agents, this study examined the discursive practices of employees with disabilities in Deliberately Developmental Organizations (DDOs). DDOs as a research site wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Second, HRD practitioners should work with organizational leaders to raise their awareness of the importance of disability inclusion and together strive to make success cases that can serve as role models for aspiring people with disabilities. Third, this study points to how the system change toward greater diversity and inclusion may benefit people with disabilities (Kwon, 2021;Kwon & Nicolaides, 2017). Especially, the participants in this study who went to domestic law schools demonstrated themselves as partial beneficiaries of such change in the South Korean legal education system.…”
Section: Practicementioning
confidence: 70%
“…Second, HRD practitioners should work with organizational leaders to raise their awareness of the importance of disability inclusion and together strive to make success cases that can serve as role models for aspiring people with disabilities. Third, this study points to how the system change toward greater diversity and inclusion may benefit people with disabilities (Kwon, 2021;Kwon & Nicolaides, 2017). Especially, the participants in this study who went to domestic law schools demonstrated themselves as partial beneficiaries of such change in the South Korean legal education system.…”
Section: Practicementioning
confidence: 70%
“…With few exceptions (Kwon, 2021; Procknow et al, 2017), the actual application of ableism in HRD literature at both conceptual and empirical has been sparse. Unlike the relatively richer development of research in HRD that theorizes and problematizes other hierarchical categories of social relations such as gender (Bierema, 2002; Callahan & Elliott, 2020), race (Byrd, 2007; Sisco, 2020), sexual orientation (Gedro & Tyler, 2014; Schmidt et al, 2012), disability has (ironically, due to its relational nature) long been out of attention in constructing shared understandings of what constitutes a legitimate organizational life.…”
Section: Areas Of Friction Within Hrdmentioning
confidence: 99%
“…There is evidence that such invitations can lead to significant organizational change in support of marginalized groups. For example, Kwon (2021) discussed how Deliberately Developmental Organizations can be leveraged to resist the able-ism often experienced by employees with disabilities. This is not to imply that members of marginalized communities must or should do extra work to educate those who occupy positions of power and privilege.…”
Section: Background To the Problemmentioning
confidence: 99%